Prediction of PVT Properties of a Sudanese Crude Oil (Block 3 and Block 7 as a Case Study) - Mohamed El-hassan Hamid, Aliya; A. Rabah, Ali (University of Khartoum Engineering Journal, 2022)
Pressure, volume and temperature (PVT) data is extensively used in the design of oil production and transportation facilities. The purpose of this study is to predict PVT properties for a Sudanese crude oil at pressures above boiling point pressure using Equations of State (EOSs). Eight of the most widely known EOSs are used; namely Patel-Teja (PT), Peng-Robinson (PR), Modified Peng-Robenson (MPR), Schmidt-Wenzel (SW), Harmens-Knapp (HK), Van Der Waal (VDW), Soave- Redlich-Kwong (SRK) and Lawal-Lake-Silberberg (LLS). For the calculation of PVT from EOSs a computer code is written using MATLAB software. To validate the prediction procedure, experimental PVT is obtained from the Ministry of Petroleum, Sudan. It represents eight (8) crude oil samples compromising 112 data points of constant mass expansion (CME) test at pressure above the boiling point.